1999
DOI: 10.1038/sj.bmt.1701618
|View full text |Cite
|
Sign up to set email alerts
|

Changes in endogenous TPO levels during mobilization chemotherapy are predictive of CD34+ megakaryocyte progenitor yield and identify patients at risk of delayed platelet engraftment post-PBPC transplant

Abstract: Summary:Patients with delayed platelet recovery post-PBPC transplant (PBPCT) are a high-risk group for thrombocytopenic bleeding and platelet transfusion dependence. Total CD34 ؉ cell dosage has been proposed as the most important factor influencing the rate of platelet recovery. To achieve the shortest time to platelet engraftment, a minimum leukapheresis target of 10 ؋ 10 6 CD34 ؉ cells/kg was established for 30 patients. Of the 29 evaluable patients, 62% had rapid (group I: time to platelets Ͼ20 ؋ 10 9 /l р… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The CD34 þ CD61 þ subsets are regarded as MK progenitors and CD34ÀCD61 þ are the major characteristics of megakaryocytes. [25][26][27] Our results showed that, on day 6, the ratio of CD34ÀCD61 þ /CD34 þ CD61 þ cells is 4.07 in miR-181a-HPCs versus 1.96 in control HPCs, which implies that miR-181a may promote the development of MK progenitors (CD34 þ CD61 þ ) to megakaryocytes (CD34ÀCD61 þ ) instead of initiating MK differentiation, as shown in Table 1.…”
Section: Resultsmentioning
confidence: 84%
“…The CD34 þ CD61 þ subsets are regarded as MK progenitors and CD34ÀCD61 þ are the major characteristics of megakaryocytes. [25][26][27] Our results showed that, on day 6, the ratio of CD34ÀCD61 þ /CD34 þ CD61 þ cells is 4.07 in miR-181a-HPCs versus 1.96 in control HPCs, which implies that miR-181a may promote the development of MK progenitors (CD34 þ CD61 þ ) to megakaryocytes (CD34ÀCD61 þ ) instead of initiating MK differentiation, as shown in Table 1.…”
Section: Resultsmentioning
confidence: 84%
“…Similarly, the number of CD34 þ CD61 þ cells has not proved useful clinically in predicting slow platelet engraftment. 1,14 When we analysed expression of CD41/CD61 in conjunction with CD34 and CD110, we could not identify a more accurate method of predicting platelet engraftment based on expression of more mature platelet markers.…”
Section: Discussionmentioning
confidence: 99%
“…In the attempt to identify the group of patients at risk for prolonged thrombocytopenia, several reports have studied a series of autografts with the aim of evaluating the effect of CD34 + lineage-specific subset numbers on time to platelet engraftment. The most significant correlation was recognized for the CD34/CD61 + megakaryocytic cell [11,53,[58][59][60][61][62]. Furthermore, in analysis of uncommitted progenitors, Baech, Johnsen 78 we discovered an inverse correlation between the CD34/CD38or CD34/CD33subset and platelet engraftment, indicating that high numbers of CD34/CD38cells, i.e., early uncommitted progenitors, may increase the risk of delayed engraftment [11,52,53,[58][59][60][61][62][63][64][65][66][67][68][69].…”
Section: The Challenge Of Cd34 + Subset Analysismentioning
confidence: 99%